2018
DOI: 10.21722/rbps.v19i2.18871
|View full text |Cite
|
Sign up to set email alerts
|

Terapia neuromotora intensiva nas habilidades motoras de criança com Síndrome de Down

Abstract: | Terapia neuromotora intensiva nas habilidades motoras de criança com Síndrome de DownRESUMO| Introdução: A Síndrome de Down (SD), ou trissomia do cromossomo 21, é a mais frequente patologia de ordem genética associada à deficiência intelectual. Objetivo: Verificar os efeitos da Terapia Neuromotora Intensiva (TNMI) nas habilidades motoras grossas em uma criança com Síndrome de Down. Métodos: Trata-se de um estudo de caso retrospectivo que avaliou uma criança de 9 anos pela Gross Motor Function Measure (GMFM)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Lima et al [26] found in their study that treatment combining conventional kinesiotherapy and the Bobath Concept provided satisfactory results for infants with DS, both in terms of muscle strengthening and proprioception, improving gross motor coordination.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lima et al [26] found in their study that treatment combining conventional kinesiotherapy and the Bobath Concept provided satisfactory results for infants with DS, both in terms of muscle strengthening and proprioception, improving gross motor coordination.…”
Section: Discussionmentioning
confidence: 98%
“…Given the above and the results obtained by the AIMS scale, it appears that early intervention programs are extremely necessary to facilitate postures and favor neuropsychomotor development [26,32]. Trindade and Nascimento [4], in their study with seven children with DS, concluded that intervention programs contribute to the reduction of motor delay in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The INMT can use orthotic garments or suit wear which offers movement resistance, and the therapy can be done in an Abiliy Unit of Exercise (AUE) using bungee cords to provide sensory stimulation, movement through resistance, standing posture and balance strategies [17] during the therapy. Most of the previous studies were performed with cerebral palsy children [14], but positive effects in gross motor skills were also showed in Down syndrome [18] and in spinal amyotrophy [19].…”
Section: Discussionmentioning
confidence: 99%
“…Em termos de desenvolvimento, a síndrome de Down, embora seja de natureza subletal, pode ser considerada geneticamente letal quando se considera que 70-80% dos casos são eliminados prematuramente (Lima et al, 2022).…”
Section: Introductionunclassified